Hemin-based conjugated effect synthesis of Fe–N/CNT catalysts for enhanced oxygen reduction. (6th April 2021) - Lu, Yue; Zhang, Han; Liu, Shaojun; Li, Chenglong; Li, Lixiang; An, Baigang; Sun, Chengguo
Abstract : Fe/N-codoped carbon nanotubes fabricated through the π–π stacking effect and olefin oxidation polymerization-induced hemin assembly on PPy shows a potential application for ORR. Abstract : Metal–nitrogen codoped cathode catalysts, such as M–N–C (M = Fe, Co, Mn, etc. ) are considered most promising non-platinum group ORR catalysts, and have received widespread attention. However, the problem involving the high oxygen reduction performance and stability of the catalyst remains to be solved. The unique olefin oxidation polymerization and π–π stacking effect induced hemin to be evenly coated on polypyrrole nanotubes (PPy). Subsequent carbonization produces the Fe–NCNT catalyst with a monodispersed, uniform diameter and large inner cavity. The PPy not only serves as a template for the formation of the hemin polymer, but also provides C, N source to further improve the catalytic activity. The material exhibits excellent ORR activity attributed to the promotion of the π–π stacking effect between hemin and PPy, and the abundant active site of Fe–N X derived from hemin. Results show that the Fe–NCNT-800 catalyst with high performance exhibits a maximum onset potential ( E onset = 0.93 V) and half-wave potential ( E 1/2 = 0.79 V). The RRDE measures points out the complete four-electron transfer pathway of the Fe–NCNT-800 catalyst. The Fe–NCNT catalysts have higher durability of a negligible negative shift (10 mV) of E 1/2 after a 5000 cycle ADT, and a remarkable methanol tolerance capability that is superior to that of the Pt/C catalyst. The synergy between the PPy-derived N-doped carbon nanotubes and Fe–N X facilitates oxygen reduction and electron conduction.